Chip-based generation of carbon nanodots via electrochemical oxidation of screen printed carbon electrodes and the applications for efficient cell imaging and electrochemiluminescence enhancement1. Issue 21 (7th June 2015) - Xu, Yuanhong; Liu, Jingquan; Zhang, Jizhen; Zong, Xidan; Jia, Xiaofang; Li, Dan; Wang, Erkang
<x xml:space="preserve">Abstract</x> A lab-on-a-chip electrochemical methodology to generate CNDs was developed. The CNDs can be used for efficient bioimaging and ECL sensor fabrication.